Thermo-oxidative stability and flammability properties of bamboo/kenaf/nanoclay/epoxy hybrid nanocomposites. Issue 37 (8th June 2020) - Chee, Siew Sand; Jawaid, Mohammad; Alothman, Othman Y.; Yahaya, Ridwan
Abstract : In this study, three types of nanoclay [halloysite nanotube (HNT), montmorillonite (MMT) and organically modified MMT (OMMT)] were incorporated into bamboo/kenaf (B/K) reinforced epoxy hybrid composites to compare their thermo-oxidative (TOD) stability and flammability properties. Abstract : In this study, three types of nanoclay [halloysite nanotube (HNT), montmorillonite (MMT) and organically modified MMT (OMMT)] were incorporated into bamboo/kenaf (B/K) reinforced epoxy hybrid composites to compare their thermo-oxidative (TOD) stability and flammability properties. B/K (50 : 50) hybrid nanocomposites were fabricated by adding 1% loading (by weight) nanoclay through a hand lay-up technique. Wide angle X-ray scattering (WAXS) and field emission scanning electron microscopy (FESEM) were used to study the morphology of the nanoclay–epoxy mixture. The TOD stability of the hybrid nanocomposites was studied with a thermogravimetry analyzer (TGA) under oxygen atmosphere. The flammability properties were evaluated using the Underwriters Laboratories 94 horizontal burning test (UL-94HB), limiting oxygen index (LOI), cone calorimetry and smoke density test. The morphological study reveals that MMT/epoxy and HNT/epoxy are highly agglomerated while OMMT/epoxy reveals a more uniform distribution morphology. The obtained results reveal that B/K/HNT shows better TOD stability below 300 °C, but B/K/MMT and B/K/OMMT show high residue content and decomposition temperatures above 300 °C. The flame retardancy of the hybrid nanocomposites improved with the loading of all types of nanoclay, but B/K/OMMT shows higher flame retardancy than B/K/MMT and B/K/HNT hybrid nanocomposites. Hybrid nanocomposites show improvement in flame properties in terms of peak heat release rate (pHRR), total heat release, fire growth rate index (FIGRA) and maximum average rate of heat emission (MARHE) and smoke growth rate index (SMOGRA) indicators. The findings from this work can be utilized to prepare high-performance fire retardant natural fiber reinforced epoxy hybrid composites for automotive and construction applications to save human lives.